A Prospective Study to Measure Drug Compliance in Epilepsy Patients - Kalyani, Padala; Goud, Merugu Shravan (Indian Journal of Pharmacy Practice)
Background: Epilepsy may promote limitations and restrain activities, interfering with the occupational ability, professional goals and social integration of patients. It increases morbidity and symptomatic epilepsy reduces life expectancy by 18 years at maximum. It continues to be a highly stigmatized and disabling chronic condition requiring a lifelong process of adherence to the prescriber’s instructions and drug regimens. But many people cannot follow the order and seizure can occur from anti-epileptic drug withdrawal. So, measuring and monitoring of drug compliance is essential. Method: Totally 75 epilepsy patients were assessed, among which 60 patients who met the inclusion criteria were recruited into the study and were interviewed by using a structured questionnaire. The survey approach was used in the study. The study period was 6 months. Results: Majority (63%) of the sample were compliant to the medication. According to the study, 27% of the sample stated cost factor as the reason for non-compliance. Among 29 (48%) patients who experienced side effects, majority (43%) suffered from drowsiness. Among 21 patients who had history of non-compliance [P-value 0.95 > 0.05 level of confidence], 90% were non-compliant in the present study. Patient counselling was done, and patients were reassessed. Conclusion: After reassessment, majority (92%) denied stopping medication in case of 2-3 months continuous absence of seizure episodes. This approach helped in 29% increment in drug compliance status among noncompliant individuals.
Keywords: Epilepsy; Structured questionnaire; Measure; Drug-compliance; Patient counselling